Attributes affecting quick service restaurants revisit intention among student of higher learning institutions / Wan Nor Farawahidah Mohd Khamis ... [et al.] - Mohd Khamis, Wan Nor Farawahidah; Jalis, Mohd Hairi; Azmi, Azila; Abd Rahman, Ahmad Esa (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
There is a growing demand for quick service restaurants worldwide. Notwithstanding the rapid growth, quick service restaurant is in a competitive industry in which the business survival depends on their ability to attract and retain their customers. Previous studies found that customers from limited buying power market segments, such as teenagers studying at higher learning institutions, often consider their food and dining experience in deciding where and what to eat. This study aims to identify the relationship between attributes of quick service restaurants, higher learning institution students’ satisfaction and their revisit intention. A self-administered questionnaire was used and distributed to 240 respondents of two higher learning institutions in Terengganu, Malaysia. Data gathered was analysed using SPSS version 21. Results showed that all six hypotheses of this study are supported. Furthermore, all variables which are food quality, service quality, ambience quality, brand image and convenience have significant relation with students’ satisfaction. From the findings, students’ satisfaction does mediate the relationship between attributes of quick service restaurants and revisit intention. Attribute of brand image appears to be the most influential factor in students’ decision on which quick service restaurants outlets they prefer to go to and dine in. Several managerial implications are discussed as guidelines for quick service restaurant operators.